A DIALOGIC SELF-STUDY OF TEACHING PRACTICES BY INTERDISCIPLINARY FACULTY: PROFESSIONAL DEVELOPMENT THROUGH TRIOETHNOGRAPHY - Akiko Takagi; Daisuke Cho; Aiko Takazawa (PUPIL: International Journal of Teaching, Education and Learning, 2026)
This study explores the professional development of three university faculty members who belong to the same faculty but specialize in different disciplines. Based on a self-study framework, the participants engaged in trioethnography to reflect on their own teaching practices. Data were collected from three recorded collaborative sessions, followed by a thematic analysis of the transcripts. The findings reveal that, while developing innovative pedagogical approaches—such as interactive group work and AI-integrated assignments—the instructors faced shared challenges. They struggled with systemic constraints specific to Japanese universities, including a lack of teaching assistants and limited transparency and coordination across syllabi and curricula. Furthermore, they encountered difficulties related to students’ passive attitudes and the complex pedagogical responses required to manage generative AI in the classroom. Ultimately, this dialogic process helped reframe personal struggles as broader structural issues, providing important psychological support against professional isolation. As a future scope, this collaborative approach can be expanded into a powerful Faculty Development tool to facilitate interdisciplinary mentoring, support early-career academics, and foster co-creation across university organizations.